Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) terhadap HASIL Belajar IPS - Tintiani, Dea Etri; Supriyanto, Supriyanto; Yuneti, Armi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aimed to determine the completeness of the social studies learning outcomes of Class V of SD Negeri 61 Lubuklinggau after implementing the Think Pair Share (TPS) cooperative learning model. This research method uses a quantitative approach with a quasi-experimental method in the One-Group Pretest-Posttest Design category. The results showed an average Pre-Test value of 47.19 and an average Post-Test of 84.69 with a percentage of 100%. Based on the t-test analysis, it was obtained that Tcount = 8.59. and Table 1.703 when compared, then Tcount ≥Ttable. With a significance level of a = 0.05. The conclusion is that the social studies learning outcomes of SD Negeri 61 Lubuklinggau class V students after implementing the Think Pair Share (TPS) cooperative learning model were significantly complete. Keywords: Learning Outcomes, Think Pair Share, Social Studies Learning